2022
DOI: 10.1038/s41598-022-15441-x
|View full text |Cite
|
Sign up to set email alerts
|

Weakened pacific overturning circulation, winter monsoon dominance and tectonism re-organized Japan Sea paleoceanography during the Late Miocene global cooling

Abstract: The Late Miocene global cooling (LMGC; approximately 7.9–5.8 Ma) was associated with remarkable changes in monsoon dynamics, biogenic bloom in the global oceans, and the rise of modern ecosystems at the expense of old biota. However, the possible linkage between the environmental changes and ecosystem shifts during the LMGC is still debated. In this paper, we show the high-resolution changes in the fluxes of selected radiolarian species, suggesting a drastic reorganization in the paleoceanography and ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 58 publications
(99 reference statements)
1
6
0
Order By: Relevance
“…Large changes can also be observed in the relative abundances of species related to PCW, dropping from 5% to <1% at ∼7.8 Ma at the onset of LMGC (Figure 2). A similar decrease between 8.0 and 7.8 Ma was recorded in PCW radiolarians from site U1425 in the Sea of Japan (Matsuzaki et al., 2022). Therefore, in the Northwest Pacific, there was likely a significant change in the North Pacific deep‐water system at the onset of LMGC.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Large changes can also be observed in the relative abundances of species related to PCW, dropping from 5% to <1% at ∼7.8 Ma at the onset of LMGC (Figure 2). A similar decrease between 8.0 and 7.8 Ma was recorded in PCW radiolarians from site U1425 in the Sea of Japan (Matsuzaki et al., 2022). Therefore, in the Northwest Pacific, there was likely a significant change in the North Pacific deep‐water system at the onset of LMGC.…”
Section: Discussionsupporting
confidence: 71%
“…Miocene deep-water circulation schemes by Holbourn et al (2013) suggest that a weakening of the ventilation of Southern Ocean intermediate water will weaken PMOC and lead to decreased productivity in PCW. Contextually, Matsuzaki et al (2022) suggested that there was a weakening of PMOC at the onset of LMGC. The results of the current study confirm this hypothesis, showing there was a decrease in PCW influence at site 1208 in the central North Pacific, and it is likely that PMOC weakened at the onset of LMGC and affected the whole Northwest Pacific.…”
Section: Late Miocene Global Cooling In Central North Pacific and Its...mentioning
confidence: 99%
See 3 more Smart Citations